UMP and SMIDEC join forces in assisting SMEs - UMP, PNC (Penerbit UMP, 2009)
The arena of entrepreneurship promises to be rewarding and profitable if company management is carried out in a systematic and effective manner. In fact, any sort of business operation should prove to be provide multiple returns if its management is skillful, knowledgeable as well as technologically savvy.